2005
DOI: 10.1007/s00192-005-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

The development of pelvic organ prolapse after colposuspension: a prospective, long-term follow-up study on the prevalence and predisposing factors

Abstract: The objectives of this prospective study were to determine the prevalence of pelvic organ prolapse (POP) after colposuspension and to investigate possible preoperative and operative risk factors. Seventy-seven women who underwent colposuspension between 1996 and 1997 were investigated. POP was assessed before colposuspension using the pelvic organ prolapse quantification system (POPQ). Women were reassessed at one and seven to eight years (or when referred with symptomatic POP). By seven to eight years, of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…However, repeat urodynamic studies postoperatively revealed a significant decrease in the maximum flow rate, which may reflect an element of outflow obstruction, although there was not significant change in the postvoid residuals and maximum detrusor pressure. The prevalence of symptomatic prolapse following colposuspension in our study is within the reported range in the literature [26]. Different theories have been proposed to explain the possible association between colposuspension and POP.…”
Section: Discussionsupporting
confidence: 71%
“…However, repeat urodynamic studies postoperatively revealed a significant decrease in the maximum flow rate, which may reflect an element of outflow obstruction, although there was not significant change in the postvoid residuals and maximum detrusor pressure. The prevalence of symptomatic prolapse following colposuspension in our study is within the reported range in the literature [26]. Different theories have been proposed to explain the possible association between colposuspension and POP.…”
Section: Discussionsupporting
confidence: 71%
“…After 8 years of follow-up, 38% had developed symptomatic prolapse and another 38% had asymptomatic prolapse. Again, BMI was not found to have a significant association with surgical failure (54). …”
Section: Resultsmentioning
confidence: 99%
“…Previously reported long‐term case series have reported an increase in symptomatic prolapse, as well as a substantial requirement for prolapse surgery following colposuspension which may be as high as 32% 19 . Our data support these findings with a high incidence of posterior vaginal wall and vault prolapse following colposuspension.…”
Section: Discussionmentioning
confidence: 99%